The Urgency Discourse of Matan and Sanad Criticism on Hadith - Alvin Noor Sahab (Qur'an and Hadith Academic Society, 2018)
As part of science, hadith studies need special attention. Therefore, there is a need for the criticism of sanad and matan hadith to be aware of its authenticity and to know the validity of a hadith. The main objective of this hadith research, in terms of both sanad as well as substance is to determine the quality of examined hadith. The quality of hadith is very important in its relation to the validity of hadith. Hadiths whose quality does not qualify cannot be used as a ḥujjah. The fulfillment of the requirement because hadith is the source of Islamic teaching. Unauthorized use of hadith can be in Islamic misplaced teachings.